Treatment of acute paraquat intoxication using recommended megadose of vitamin C: A reappraisal. (December 2013) - Chang, J.-B.; Lin, C.-C.; Chiou, J.-F.; Mau, S.-Y.; Liu, T.-Z.; Chen, C.-H.
Abstract: Megadose of vitamin C (MVC) has been proposed for an emergent treatment of acute paraquat (PQ) poisoning. However, the safety issue of this treatment protocol has not been evaluated. Here, we present the first evidence that vitamin C can promote aggravated production of hydroxyl radical (OH ) via interacting with preexisting PQ + /H2 O2 system in a nonmetal-catalyzed manner. This enhanced oxidative stress would therefore expect to cause more deleterious effect during acute PQ intoxication. To lend support to this possibility, we set out to attest the effects of MVC on a simulated, PQ-intoxicated, Madin–Darby canine kidney (MDCK) cell model. First, PQ alone could trigger oxidative–nitrosative stress (ONS) through robust generation of reactive oxygen species and nitric oxide (NO) that could induce apoptotic killing via promoting effective release of mitochondrial cytochrome c, an apoptogenic factor. The percentage of apoptosis for MDCK cells treated with 1.0 mM PQ for 24 h was 16.3 ± 13.0%. However, when MDCK cells were treated with a combination of PQ (1.0 mM) and MVC (20 mM) for 24 h, the severity of apoptotic killing was further exacerbated as reflected by a nearly 7-fold increase in the release of mitochondrial cytochrome c and the percentage of apoptotic cell population rose sharply to 90.7 ± 5.1%. These data indicate that MVC apparently exacerbates further killing rather than cytoprotection on this simulated, PQ-intoxicated MDCK cell model and suggest that the treatment of PQ poisoning using MVC protocol should be cautious.